NQO1 C609T polymorphism correlated to colon cancer risk in farmers from western region of Inner Mongolia - Su, Xiu-Lan; Yan, Mei-Rong; Yang, Ling; -Suyila, Qimuge (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To investigate the relationship between NAD(P)H:quinone oxidoreductase 1 (NQO1) C609T polymorphism and colon cancer risk in farmers from western region of Inner Mongolia. Methods: Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was performed to analyze NQO1 C609T polymorphism from 160 healthy controls and 76 colon cancer patients. Results: Among the colon cancer patients, the incidence of NQO1 T allele (53.29%) was significantly higher than it in control group (33.75%, P